PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN HUTANG (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Kosmetik dan Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia 2013-2018): kris - Kristanti Rahman; Febriana Respati Anindita; Febriana Respati Anindita (JURNAL EKONOMI, 2020)
The purpose of every company management is to maximize the prosperity of the owner of the company. In realizing these goals often a company faces various problems, including three main problems that are interrelated with one another. These problems include investment decisions, funding policies, and policies in determining how much dividend the company must distribute to shareholders.The funding policy is one of the most important policies for the company because it involves obtaining sources of funds for the company’s operational activities. The research aimed to knowing influencing of Dividend Payout Ratio (X1), Company Growth (X2), Sales Growth (X3) on Debt Policy. Data used in this reasearch are ManufacturingCompanies in the Cosmetics and Household. The period of this research is for 6 years, started from 2013 until 2018 for was data of Manufacturing Companies in the Cosmetics and Household. The sampel selected by purposive sampling method. The type of data used is secondary data and total sample used in this research is 24 companies that have been selected based on predetermined criteria. Methods of data analysis used is multiple linear regression. The results of this research indicate that : 1. Dividen Payout Ratio affect Debt Policy. Company Growthdoesn’t affects Debt Policy . 3. Sales Growth doesn’t affects Debt Policy. Further research is recommended that can expand the research sample, add variables and extend the periodde of research.